The conversation on gender diversity - Gill-Peterson, Jules (Baltimore, USA: Johns Hopkins University Press, 2023)
"This book collects articles from nonprofit, independent news organization, The Conversation, to present an important primer on the history of gender diversity and the current challenges transgender people face in American society"--
"From contributors to The Conversation, a look at gender diversity in the twenty-first century and the intricate and intersecting challenges faced by trans and nonbinary people.With media amplifying the voices of anti-trans legislators and critics, it is important to turn to the stories, research, and expertise of trans and nonbinary people in order to understand the reality of their experiences. In The Conversation on Gender Diversity, editor Jules Gill-Peterson assembles essential essays from The Conversation U.S. by experts on gender diversity. The essays guide readers through seldom-covered aspects of transgender history and present an overview of the social and political barriers that disenfranchise trans people and attempt to remove them from public life. As these essays collectively show, trans and nonbinary people may be forced to be the face of gender and its diversity, but the cultural, political, and social realities of gender connect-and subject-everyone. Despite these challenges, there is an immense culture of love and support across the queer community that is bolstered by activists and allies working against transphobic attacks. Trans and gender-diverse youth are growing up in a world filled with ever-increasing hurdles and rising danger, even with the contemporary public recognition of trans life in culture and media. But they are not facing these challenges alone.The Critical Conversations series collects relevant essays from top scholars on timely topics, including water, biotechnology, gender diversity, gun culture, and more, originally published on the independent news site The Conversation U.S. Contributors: Robert L. Abreu, Catherine Armstrong, Stacy Branham, Christopher Carpenter, L. F. Carver, Mandy Coles, Arin Collin, George B. Cunningham, Avery Dame-Griff, Jules Gill-Peterson, Abbie Goldberg, Gilbert Gonzales, Frances Grimstad, Foad Hamidi, Elizabeth Heineman, Glen Hosking, Bethany Grace Howe, Jay A. Irwin, Shanna K. Kattari, Kacie Kidd, Terry Kogan, Vanessa LoBue, Gabriel Lockett, Megan K. Maas, Julie Manning Magid, Em Matsuno, Tey Meadow, Kyl Myers, Madeleine Pape, Ruth Pearce, Jae A. Puckett, Samantha G. Rosenthal, Morgan Klaus Scheuerman, Elizabeth A. Sharrow, Carl Sheperis, Donna Sheperis, stef m. shuster, Jules Sostre, Ryan Storr, Carl Streed, Diana M. Tordoff, Travers"--
Includes bibliographical references.
Keywords: Transgender people -- United States; Gender identity -- United States; Gender-nonconforming people -- United States; SOCIAL SCIENCE / Gender Studies; POLITICAL SCIENCE / Public Policy / Social Policy